A Study of Studentsâ€™ Perception on The Use Facebook Group in Improving Writing - Jamal, Muhammad Kamaruddin (Journal of Teaching of English, 2019)
This study attempts to know the studentsâ€™ perception on a Facebook group in improving writing skill on the tenth grade of SMA 5 Kendari that focus on enhancing students writing performance level and the brainstorm ideas at the pre-writing stage. Also, to find out how Facebook influence the studentsâ€™ affective domain. The researcher employed mix method design with questionnaire as instrument to collect data from 36 students. The data was analyzed by calculating the frequency distribution of Likert Â scale. Â The Â result Â reveals Â there Â was Â positiveÂ  perception Â among Â students Â about Â applying Facebook Group in improving writing. Particularly, Respondent (89.7%) spell â€“ check feature helps students to avoid the error spelling and (91.6) student feel motivated when they got â€œlikeâ€ from their friends. Â It Â is Â suggested Â that Â futureÂ  research Â to Â investigate Â the Â teacher Â and Â studentsâ€™ Â problem Â in applying Facebook. In addition, the future study researcher may investigate the use Facebook Group in another skill of English.Â Â  Lastly, the future study may investigation the use other SNS not only Facebook but it can be Path, Twitter, or Instagram.Â Keywords: Facebook Group, Perception, Writing